EN-LAKP: Lightweight Authentication and Key Agreement Protocol for Emerging Networks - Anand, Nemalikanti; Saifulla, M A (IEEE access, 2023)
In the next generation, emerging network technologies like Software Defined Networking (SDN) and Wireless Sensor Networks (WSNs) will be developed and deployed to improve computing facilities. Micro-electromechanical system technologies advance, and WSNs gain in popularity because they provide real-time monitoring solutions that are both economically and practically viable. The SDN paradigm is consequently being incorporated into WSN to prevent a performance bottleneck with traditional network architecture as network traffic and diverse sensor nodes increase. Because they interact through a public channel and the sensor nodes are spread throughout a hostile environment, the information transmitted among entities is subject to assault. The proposed protocol showed how centralized SDN controller nodes logically assumed the role of network management and control. Therefore, we present a lightweight authentication and key agreement mechanism for SDN-enabled wireless sensor networks to protect entity communication. Additionally, we demonstrate that the suggested system prevents known security flaws by conducting both informal and formal security studies using the Scyther tool and BAN logic. Further, the performance study demonstrates that the suggested scheme performs better in computing and communication burdens than related protocols with 1.6% to 5.4% and 1.3% to 5.8%, respectively.